2018
DOI: 10.1159/000487546
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet for Treatment of Chronic Kidney Disease-Mineral and Bone Disorder: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Cinacalcet could decrease serum calcium, phosphate, and parathyroid hormone (PTH) in previous meta-analyses. However, the effect of cinacalcet on the new biomarkers such as fibroblast growth factor-23 (FGF-23), bone markers, and vascular calcification are still unestablished. We conducted a meta-analysis to examine the effects of cinacalcet on all laboratory and clinical spectrums of chronic kidney disease-mineral bone disorders (CKD-MBD). Methods: A systematic literature search was conducted in ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
13
0
6
Order By: Relevance
“…Serum FGF-23 is associated with left ventricular hypertrophy and has been linked to an increased risk for cardiovascular mortality [2,3,32]. Although a recent meta-analysis demonstrated that cinacalcet can decrease serum FGF-23, most included studies were performed in nonsevere SHPT (serum iPTH levels below 1000 pg/mL) [13]. The present study illustrated that cinacalcet can still reduce serum FGF-23 in chronic HD patients with the median serum iPTH levels of around 1400 pg/mL (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Serum FGF-23 is associated with left ventricular hypertrophy and has been linked to an increased risk for cardiovascular mortality [2,3,32]. Although a recent meta-analysis demonstrated that cinacalcet can decrease serum FGF-23, most included studies were performed in nonsevere SHPT (serum iPTH levels below 1000 pg/mL) [13]. The present study illustrated that cinacalcet can still reduce serum FGF-23 in chronic HD patients with the median serum iPTH levels of around 1400 pg/mL (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies showed that treatment with cinacalcet is associated with a decrease of serum PTH, calcium, and phosphate levels, although moderately (30). A meta-analysis including over ten thousand ESRD patients found that cinacalcet significantly reduces PTH concentrations (weighted mean difference −22 pmol/L), calcium levels (weighted mean difference −0.7 mmol/L), and phosphate levels (weighted mean difference of −0.4 mmol/L) (31). Circulating FGF-23 levels also decrease significantly with cinacalcet treatment compared to vitamin D therapy alone (median change −40% (−63% to 16%), p < 0.001) (32).…”
Section: Therapeutic Pharmacological Optionsmentioning
confidence: 99%
“…Cinacalcet and vitamin D as monotherapies or in combination are common treatments for SHPT in patients with CKD, aimed at achieving clinically acceptable levels of PTH and maintaining control of calcium and phosphorus levels. Numerous trials have documented the efficacy of these three regimens for the treatment of SHPT (20,30,(37)(38)(39)(40). However, there are currently two challenging questions facing the medical community with regard to these treatments.…”
Section: Discussionmentioning
confidence: 99%